Drop Rawls?. Issue 1 (29th August 2021) - Dierksmeier, Claus
Abstract: Business ethicists disagree on whether John Rawls's political philosophy can be applied to their questions and concerns. They concur, however, that, if warranted, such an application of his theory would be highly instructive for the field. This article scrutinizes that assumption. The paper examines to what extent a normative import of Rawls's philosophy into business ethics would indeed render adequate results. Highlighting shortcomings of Rawls in regard to several pressing concerns of contemporary business ethics, the paper ponders whether, for purposes of normative guidance and conceptual orientation, Rawls's theory can meet the expectations that its adherents foster.